Slit/Robo-Mediated Chemorepulsion of Vagal Sensory Axons in the Fetal Gut - Goldberg, David (2012)
BACKGROUND: The vagus nerve descends from the brain to the gut during fetal life to reach specific targets in the bowel wall. Vagal sensory axons have been shown to respond to the axon guidance molecule netrin and to its receptor, deleted in colorectal cancer (DCC). As there are regions of the gut wall into which vagal axons do and do not extend, it is likely that a combination of attractive and repellent cues are involved in how vagal axons reach specific targets. We tested the hypothesis that Slit/Robo chemorepulsion can contribute to the restriction of vagal sensory axons to specific targets in the gut wall. RESULTS: Transcripts encoding Robo1 and Robo2 were expressed in the nodose ganglia throughout development and mRNA encoding the Robo ligands Slit1, Slit2, and Slit3 were all found in the fetal and adult bowel. Slit2 protein was located in the outer gut mesenchyme in regions that partially overlap with the secretion of netrin-1. Neurites extending from explanted nodose ganglia were repelled by Slit2. CONCLUSIONS: These observations suggest that vagal sensory axons are responsive to Slit proteins and are thus repelled by Slits secreted in the gut wall and prevented from reaching inappropriate targets.